Staying Connected to your Athletes during COVID-19 through Virtual Training - Glenn Corcoran; Rick Martin; Patricia Sullivan (International Universities Strength and Conditioning Association, 2020)
Providing training options for teams and squads that train at the Bond University High Performance Training Centre during COVID-19 isolation and social distancing requirements, to ensure they remain physically active and in preparedness for return to weight room lifting.